Book Review: The Moody Handbook of Theology - Obed Wahyu Setiawan; Nugroho, Hana Adji (Sekolah Tinggi Teologi Baptis Indonesia, 2024)
In this book, Dr. Paul Enns combines all of things about theology, including all the theological methods. The author begins with biblical theology, then continues with studies of systematic theology, historical theology, dogmatic theology, and contemporary theology. Paul Enns explains and demonstrates these categories, and carefully evaluates each point in the light of God's Word. Biblical Theology is the study of doctrines in the Holy Bible according to developments in each era or according to the literature of each author, based on a chronological framework in the Bible. Systematic Theology is the study of doctrines from the Holy Bible, which are arranged and arranged based on themes from data obtained from the entire Bible. Historical Theology is the study of Christian religious doctrines that have been progressively debated, modified, and articulated by individuals or groups throughout the centuries since the end of the apostolic era. Dogmatic Theology is the study of the doctrines of Christian groups throughout church history, which have been systematized based on exclusive hermeneutical boundaries. Contemporary Theology is the study of the doctrines of Christian groups, which have developed in the twentieth century.